Umbilicoplasty in children with huge umbilical hernia - Akakpo-Numado Gamedzi Komlatsè; Mihluedo-Agbolan Komlan Anani; Boume Missoki Azanledji; Adabra Komlan; Gnassingbe Komla; Tekou Hubert (Wolters Kluwer Medknow Publications, 2014)
Background: Huge umbilical hernias (HUH) are voluminous umbilical hernia (UH) that are frequent in black African children. Several surgical techniques are used in their treatment for umbilical reconstruction, but techniques using skin flaps provide better aesthetic results. In this study, we presented our technique of umbilicoplasty in HUH, and its results. Patients and Methods: It is a retrospective study on children treated for HUH, from January 2012 to December 2013. The UH was called HUH when its basis diameter (BD) exceeds 3 cm. Every HUH was characterised by its height, BD and morphology. Our technique was a two lateral flaps technique; the flaps are symmetrical and drawn so as to reconstitute the different parts of the umbilicus. The results were appreciated with criteria, including the peripheral ring and the central depression of the neo-umbilicus. Results : Twelve children were concerned (7 boys and 5 girls). Their mean age was 5 years and 6 months. The mean BD was 5.6 cm (extremes 3 and 8 cm), and the mean height of the HUH was 7.45 cm (extremes 3 and 9 cm). All underwent umbilicoplasty. In early post-operative period, two children presented a transitory subcutaneous hematoma. Late complications were granulation tissue with two children, and cheloid scar with one. With a mean follow-up of 10 months, we had 10 excellent results and two fair results according to our criteria. Conclusion: Our two lateral flaps umbilicoplasty is well-adapted to HUH in children. It is simple and assures a satisfactory anatomical and cosmetic result.